Kajian Mengenai Privasi dalam Informasi Digital Dihubungkan dengan Directive 95/46/EC dan Directive 2002/58/EC of The European Parliament and of The Council - Tansah Rahmatullah (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2017)
Information and Communication Technology has played a major role in the process of receiving, sending, and storing data, both public data and privacy data in various fields. But unfortunately, the empowerment of Information and Communication Technology related to personal data or privacy is starting to run out of control. Conditions that occur at this time are the emergence of misuse of personal data or violations of privacy so that the impact can be detrimental to the community as a user. This study uses normative legal research methods using a normative juridical approach which is carried out by reviewing and analyzing the rules of international law relating to the privacy of digital information. Based on the research, it was found that privacy is not only protected by law but also includes cultural norms, ethics, and business / professional practices. DIRECTIVE 95/46 / EC and DIRECTIVE 2002/58 / EC provide protection against data and privacy in the digital era and answer a number of important issues related to information confidentiality, treatment of data traffic, spam and cookies. In addition, it also provides guidelines and explanations that the processing of personal data can only be done for relevant and not excessive purposes, for legitimate purposes, as well as ensuring the processing of personal data accurately and up to date.